Attributes facilitating solid waste separation at source practice among household - Nur Azzlin Mangsor, 1990- , author 610953; Low, Sheau Ting, supervisor 608714; Fakulti Geoinformasi dan Harta Tanah 555724 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Pengurusan Aset dan Fasiliti)